2020
DOI: 10.1038/s41598-020-66192-6
|View full text |Cite
|
Sign up to set email alerts
|

The mechanoelectrical transducer channel is not required for regulation of cochlear blood flow during loud sound exposure in mice

Abstract: The mammalian cochlea possesses unique acoustic sensitivity due to a mechanoelectrical 'amplifier', which requires the metabolic support of the cochlear lateral wall. Loud sound exposure sufficient to induce permanent hearing damage causes cochlear blood flow reduction, which may contribute to hearing loss. However, sensory epithelium involvement in the cochlear blood flow regulation pathway is not fully described. We hypothesize that genetic manipulation of the mechanoelectrical transducer complex will abolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…After noise exposure, dexmedetomidine displayed protective effects against NIHL [ 47 ]. In mice, manipulation of adrenergic inputs to the cochlea confirmed that SNS regulates cochlear blood flow in response to intense loud sound exposure [ 48 ]. However, these findings are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…After noise exposure, dexmedetomidine displayed protective effects against NIHL [ 47 ]. In mice, manipulation of adrenergic inputs to the cochlea confirmed that SNS regulates cochlear blood flow in response to intense loud sound exposure [ 48 ]. However, these findings are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in vivo live cochlear imaging using two-photon microscopy revealed that the gentamicin transporter, expressed in the SV and involved in the blood−labyrinthine−barrier function, protects against gentamicin-induced hearing loss, which causes drug-induced hearing loss in a significant patient population (Kim and Ricci 2022 ). Including drug-induced hearing loss, SV is an important component because sound exposure, which causes noise-induced hearing loss, decreases SV blood flow (Burwood et al 2020 ). Previous reports have revealed cochlear blood vessel details.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating arteriole diameter, the vessel-associated component has a significant effect on CBF [Brechtelsbauer et al, 1990;Laurikainen et al, 1993Laurikainen et al, , 1997Ren et al, 1993b]. Disruption of the sympathetic nervous system partially abolished, found that sympathetic activation contributes to sound-induced reduction of CBF [Burwood et al, 2020]. Unilateral and bilateral SG blockade resulted in effects of differing magnitude on CBF on each side, although both resulted in an increase in CBF.…”
Section: Sympathetic Activity and Peripheral Auditory Systemmentioning
confidence: 98%